From Soil to Self: Existential Identity in "The Good Earth" by Pearl S. Buck - Karki, Govinda Bahadur (Community College Research Journal, 2025)
This study explores existentialism in Pearl S. Buck’s The Good Earth, set in pre-revolutionary agrarian China. It examines how themes of individual agency, meaning-making, and endurance appear in the lives of Wang Lung and his family, who navigate a society shaped by feudal customs, poverty, and patriarchal norms. Using a qualitative textual analysis grounded in existentialist theory, the research considers characters both as individual agents and as products of broader cultural and historical forces. Findings reveal that the novel highlights core existential concerns such as authenticity, freedom, and responsibility even within a collectivist, non-Western context. The study demonstrates the universality of existential dilemmas and shows how literature can express human resilience and dignity. Ultimately, Buck portrays rural Chinese life as a space where human existence remains meaningful despite hardship and social constraints.